Pengaruh Fashion Involvement, Shopping Lifestyle, dan Sales Promotion terhadap Impulse Buying pada Pengguna E-commerce - Padmasari, Dwi; Widyastuti, Widyastuti (Jurnal Ilmu Manajemen, 2022)
Health products are no longer the most sought after product but a well-known fashion product in e-commerce. This study discusses the involvement of fashion, shopping lifestyle, sales promotion on impulse buying. This study uses a quantitative method with a causal research design. The survey data used in this study came from respondents’ responses and the literature. Respondent data was collected using google forms. The measurement scale uses a Likert scale of one to five points. Point one indicates strongly disagree, and five means strongly agree. The sample of this research is 150 respondents. Statistical analysis used is multiple linear regression. This study shows that fashion, shopping lifestyle, and sales promotion significantly affect impulse buying of fashion products in Shopee e-commerce. Shopee and fashion product sellers can use the results of this research to improve promotional programs so that more consumers are interested and make purchases suddenly because of the sales promotions offered.